2012
DOI: 10.2478/v10213-012-0026-0
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Study on the Safety of a New Vaccine Against Canine Babesiosis Containing Soluble Parasitic Antigen (SPA)

Abstract: The aim of this study was to assess the safety of a new vaccine, containing soluble parasitic antigen (SPA), against canine babesiosis. Fifteen dogs were included in the experiment. Five controls received only the adjuvant and 10 dogs were vaccinated with Babesia canis canis SPA twice, at a two weeks interval. For the whole period of the study all animals were under constant clinical observation. Haematological and biochemical tests were performed. Flu-like symptoms and local reactions at the injection site we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The fraction appeared to be strongly immunogenic, which was confirmed in Western blot tests. It was the proteins of 51–52 kDa that caused the strongest reaction with serum samples obtained from the dogs vaccinated with SPA (Adaszek et al 2012a , b ). Considering the above, it may be inferred that these proteins are released into a dog’s serum by the protozoa after infection and they result in a signal in the infected dogs’ serum, which may then be treated as a disease marker.…”
Section: Resultsmentioning
confidence: 99%
“…The fraction appeared to be strongly immunogenic, which was confirmed in Western blot tests. It was the proteins of 51–52 kDa that caused the strongest reaction with serum samples obtained from the dogs vaccinated with SPA (Adaszek et al 2012a , b ). Considering the above, it may be inferred that these proteins are released into a dog’s serum by the protozoa after infection and they result in a signal in the infected dogs’ serum, which may then be treated as a disease marker.…”
Section: Resultsmentioning
confidence: 99%
“…Studies on the use of soluble parasite antigens (SPA) from plasma of Babesia-infected animals or derived from in vitro cultures of Babesia organisms in immunoprophylaxis of babesiosis have been in progress for quite some time (5,15,16,(22)(23)(24). Early observations showed that vaccinations with SPA protected dogs against the development of a critical pathological process characterised by a decrease in packed cell volumes and retention of infected erythrocytes in the microvasculature (18).…”
mentioning
confidence: 99%